Orthodontic treatment of a Class III patient with periodontal attachment loss, agenesis and dental transposition. A case report - Alfaro Ramos, Giancarlo (2018)
A fundamental aspect in the treatment of orthodontics is the correct use of biomechanics; especially in patients who present loss of periodontal insertion and conditions such as agenesis and dental transposition. This article reports the treatment of a 24-year-old female patient, who presented a Class III malocclusion; which was corrected obtaining a stable and functional occlusion, as well as the reduction of the initial occlusal trauma. Additionally, the aesthetics was improved throughout the antero-superior sector; which was caused by the imbalance left by the central incisor’s agenesis and the transposition of the canine.